Improving Marketing strategies of An-Nahl Honey Bee Farm Products through E-Commerce Marketing on An-Nahl’s Website - Sri Utami; Ani Sulistyarsi; Abd. Rohman Taufiq; Yudha Adi Kusuma (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
The An-Nahl honey bee farm of the Madiun Group, owned by Mr Sunardi, is located in the Musir Hamlet, Banjarsari Wetan Village, Dagangan District, Madiun Regency, and was started in 2000. The main products produced are honey, royal jelly, bee pollen, and solid propolis. The honey was collected from the flowers of calliandra, mango, kapok, rambutan, narra, bay leaf, water spinach, and rubber. An-Nahl honey bee farm already has a business license, namely PIRT No. 10953519010730 – 20. Its honey has become a superior product in Banjarsari Wetan Village, Dagangan District, Madiun Regency since 2016. Despite the success in its production, the AnNahl honey bee farm faced marketing problems. It is still using conventional marketing techniques. Product distribution is carried out only in the Madiun area. Moreover, the level of sales was considered as low less than ten bottles per month. The farm needed to advance its marketing strategy by expanding marketing media as a solution. The method of carrying out the community service activities were through a workshop on social media, training and assisting media social marketing course, and evaluating the programs. The study result shows that the material provided was a fresh material for participants with percentage of understanding increasing by 52% and above 113% for each type of honey volume in sales. Therefore, this program was successful in providing new knowledge to honey bee farmers in social media marketing strategy. The farm is also expecting this program to be continued.